Comparison of Waterfront City Concept Implementation Strategies in Ambon City and Kupang City: Perbandingan Strategi Penerapan Konsep Waterfront City di Kota Ambon dan Kota Kupang - Abdul Muin; Heinrich Rakuasa (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
The concept of waterfront city is a development concept that can be applied by areas located in coastal areas. Ambon City and Kupang City as areas in the coastal area also developed the concept of waterfront city. The strategies used in implementing the concept of waterfront city in Ambon City and Kupang City have similarities and differences, because they must be adjusted to the conditions of the area and the purpose and function of its designation. Ambon City develops the concept of waterfront city by dividing the Ambon City area into 4 Development Area Units (SWP) while still considering the needs of the community, while Kupang City develops the concept of waterfront city by considering aspects of community economic activity, environmental sustainability and provision of public facilities. The similarity between Ambon City and Kupang City is that as a national activity center (SPN) area, it still accommodates the interests of the community